2019
DOI: 10.20944/preprints201902.0124.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ligand-Protein Interactions: A Hybrid ab initio/Molecular Mechanics Computational Study

Abstract: Cyclooxygenases (COX), or prostaglandin endoperoxide synthases (PTGS), are key enzimes in the synthesis of prostaglandins, which are chemical species critical in mediating inflammatory processes. There are two highly homologous COX isoforms: COX-1 and COX-2. COX-1 is involved in the production of prostaglandins, chemical compuounds that take part in physiological processes such as: protection of the gastric epithelium, maintenance of renal flow, platelet aggregation, neutrophil migration and, also, are express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Compare to affinity character between chlorogenic acid and COX-2 in this research indicated that interaction was blocking at COX2 in different active site location compare to other ligands. Therefore Chlorogenic acid and isomers are competitive inhibitors [12]. Different binding sides in COX-2 have a potential role for inhibiting COX-2 function in different effects compared to chemical drugs.…”
Section: Interactionmentioning
confidence: 99%
“…Compare to affinity character between chlorogenic acid and COX-2 in this research indicated that interaction was blocking at COX2 in different active site location compare to other ligands. Therefore Chlorogenic acid and isomers are competitive inhibitors [12]. Different binding sides in COX-2 have a potential role for inhibiting COX-2 function in different effects compared to chemical drugs.…”
Section: Interactionmentioning
confidence: 99%